Ethnobiological Study of Wiwitan in the Somongari Javanese Community as Biodiversity Learning through Educational Video - Fajar Adinugraha (Postgraduate, University of Mataram, 2024)
The lack in knowledge of biodiversity's value at a young age accompanies the loss of biodiversit can be overcome with indigenous knowledge. Wiwitan is a form of indigenous knowledge that takes the form of a Thanksgiving prayer held prior to the commencement of the harvest season. This tradition serves to demonstrate the value placed on biodiversity, with the spiritual value of ubarampe, or offerings. Ubarampe is a traditional ritual apparatus that employs biodiversity, including plants and animals. Nevertheless, the knowledge associated with ubarampe remains predominantly oral and demonstrative, with no documented research or written records. The study aimed to investigate the ritual of Wiwitan, its ubarampe, the spiritual value, and utilization of organisms. Additionally, the purpose of this study is to depict educational videos that enhance comprehension and appreciation of the biodiversity value of the ubarampe in the Wiwitan ritual. The research technique employed ethnobiological principles during field exploration. The findings revealed that eleven types of ubarampe were utilized with eighteen plant species. The informative videos are available on the following YouTube link: https://youtu.be/Ld7LgjMNH8Y. Creating educational video and uploaded it on YouTube presents an alternative means of promoting the biodiversity value of the Wiwitan ritual.